Bedside calculation of mechanical power during volume- and pressure-controlled mechanical ventilation - Davide Chiumello; Miriam Gotti; Mariateresa Guanziroli; Paolo Formenti; Michele Umbrello; Iacopo Pasticci; Giovanni Mistraletti; Mattia Busana (Critical Care, 2020)
Abstract Background Mechanical power (MP) is the energy delivered to the respiratory system over time during mechanical ventilation. Our aim was to compare the currently available methods to calculate MP during volume- and pressure-controlled ventilation, comparing different equations with the geometric reference method, to understand whether the easier to use surrogate formulas were suitable for the everyday clinical practice. This would warrant a more widespread use of mechanical power to promote lung protection. Methods Forty respiratory failure patients, sedated and paralyzed for clinical reasons, were ventilated in volume-controlled ventilation, at two inspiratory flows (30 and 60 L/min), and pressure-controlled ventilation with a similar tidal volume. Mechanical power was computed both with the geometric method, as the area between the inspiratory limb of the airway pressure and the volume, and with two algebraic methods, a comprehensive and a surrogate formula. Results The bias between the MP computed by the geometric method and by the comprehensive algebraic method during volume-controlled ventilation was respectively 0.053 (0.77, − 0.81) J/min and − 0.4 (0.70, − 1.50) J/min at low and high flows (r 2 = 0.96 and 0.97, p < 0.01). The MP measured and computed by the two methods were highly correlated (r 2 = 0.95 and 0.94, p < 0.01) with a bias of − 0.0074 (0.91, − 0.93) and − 1.0 (0.45, − 2.52) J/min at high-low flows. During pressure-controlled ventilation, the bias between the MP measured and the one calculated with the comprehensive and simplified methods was correlated (r 2 = 0.81, 0.94, p < 0.01) with mean differences of − 0.001 (2.05, − 2.05) and − 0.81 (2.11, − 0.48) J/min. Conclusions Both for volume-controlled and pressure-controlled ventilation, the surrogate formulas approximate the reference method well enough to warrant their use in the everyday clinical practice. Given that these formulas require nothing more than the variables already displayed by the intensive care ventilator, a more widespread use of mechanical power should be encouraged to promote lung protection against ventilator-induced lung injury.